Evaluation of the OSA treatment protocol in syndromic craniosynostosis during the first 6 years of life. Issue 10 (October 2021) - de Goederen, Robbin; Yang, Sumin; Pullens, Bas; Wolvius, Eppo B.; Joosten, Koen F.M.; Mathijssen, Irene M.J.
Summery: Introduction: Obstructive sleep apnea (OSA) is frequently present in patients with syndromic craniosynostosis. The aim of this study is to determine the long-term effectiveness of our OSA treatment protocol in our tertiary center in a cohort of children with syndromic craniosynostosis. Methods: Children with syndromic craniosynostosis born between January 2005 and December 2013 were eligible for inclusion ( n  = 114). Data from ambulatory and inhospital polysomnographies were used. The obstructive-apnea/hypopnea index was used for OSA classification. Results: Polysomnographies were performed in 83 patients. Mild OSA was diagnosed in 19, moderate in six, and severe in seven children. Of the 32 patients with OSA, 12 patients (37.5%) initially received expectant care of which OSA resolved spontaneously in nine without recurrence. Twenty patients were surgically treated. Adenotonsillectomy (ATE) had a 90% success rate with no OSA recurrence. Monobloc surgery was performed in four patients with mild OSA, although not OSA-indicated. Monobloc was performed for moderate or severe OSA in six patients, in four patients in combination with ATE and with mandibular distraction in one. Monobloc surgery for moderate or severe OSA had a 100% success rate in treating OSA and decannulation. Conclusion: Expectant care is often sufficient to resolve mild OSA in patients with syndromic craniosynostosis, and should also be considered in patients with moderate OSA with close follow-up. ATE has an important role in the OSA treatment protocol. Monobloc surgery, combined with mandibular distraction on indication, is effective in resolving moderate to severe OSA with a stable long-term result.